Combined isosorbide dinitrate and ibuprofen as a novel therapy for muscular dystrophies: evidence from Phase I studies in healthy volunteers - Cossu MV; Cattaneo D; Fucile S; Pellegrino P; Baldelli S; Cozzi V; Capetti A; Clementi E (Dove Medical Press, 2014)
Maria Vittoria Cossu,1 Dario Cattaneo,1 Serena Fucile,1 Paolo Pellegrino,1 Sara Baldelli,1 Valeria Cozzi,1 Amedeo Capetti,2 Emilio Clementi1,3 1Unit of Clinical Pharmacology, Consiglio Nazionale delle Ricerche Institute of Neuroscience, Department of Biomedical and Clinical Sciences, University Hospital “Luigi Sacco”, Università di Milano, Milan, Italy; 2Unit of Infectious Diseases, University Hospital “Luigi Sacco”, Milan, Italy; 3Scientific Institute, IRCCS Eugenio Medea, Bosisio Parini, Lecco, Italy Abstract: We designed two Phase I studies that assessed healthy volunteers in order to evaluate the safety and to optimize the dosing of the combination of the drugs isosorbide dinitrate, a nitric oxide donor, and ibuprofen, a nonsteroidal antiinflammatory drug. We designed these studies with the aim of designing a Phase II trial to evaluate the drugs’ efficacy in patients affected by Duchenne muscular dystrophy. For the first trial, ISOFEN1, a single-dose, randomized-sequence, open-label, active control, three-treatment cross-over study, was aimed at comparing the pharmacokinetics of ibuprofen 200 mg and isosorbide dinitrate 20 mg when given alone and concomitantly. The pharmacokinetics of ibuprofen given alone versus ibuprofen given concomitantly with isosorbide dinitrate were similar, as documented by the lack of statistically significant differences in the main drug’s pharmacokinetic parameters (time to maximal concentration [Tmax], maximal concentration [Cmax], area under the curve [AUC]0–t, and AUC0–∞). Similarly, we found that the coadministration of ibuprofen did not significantly affect the pharmacokinetics of isosorbide dinitrate. No issues of safety were detected. The second trial, ISOFEN2, was a single-site, dose titration study that was designed to select the maximum tolerated dose for isosorbide dinitrate when coadministered with ibuprofen. Eighteen out of the 19 enrolled subjects tolerated the treatment well, and they completed the study at the highest dose of isosorbide dinitrate applied (80 mg/day). One subject voluntarily decided to reduce the dose of isosorbide dinitrate from 80 mg to 60 mg. The treatment-related adverse events recorded during the study were, for the large majority, episodes of headache that remitted spontaneously in 0.5–1 hour – a known side effect of isosorbide dinitrate. These studies demonstrate that the combination of isosorbide dinitrate and ibuprofen does not lead to pharmacokinetic interactions between the two drugs; they also demonstrate that the combination of isosorbide dinitrate and ibuprofen has optimal tolerability and safety profiles that are similar to those previously reported for isosorbide dinitrate and ibuprofen given alone. Keywords: coadministration, pharmacokinetic profile, adverse events, ibuprofen, isosorbide dinitrate